Highly sensitive determination of anesthetic drug benzocaine based on hydroxypropyl-β-cyclodextrin–carbon black nanohybrids. Issue 9 (15th February 2022) - Wang, Zengchun; Yu, Lingshan; Huang, Yu; Chen, Ye; Cao, Hua
Abstract : Preparation of HP-β-CD–CB and its application for the electrochemical detection of BZC. Abstract : Benzocaine (BZC) is a local anaesthetic drug coupled with numerous adverse effects, and thus poses a great challenge for its simple and highly sensitive detection. For resolving this issue, hydroxypropyl-β-cyclodextrin–carbon black (HP-β-CD–CB) nanohybrid that possesses the collaborative advantages of CB ( e.g., excellent electrical properties, large surface area) and HP-β-CD ( e.g., high molecule recognition and preconcentration capability) was synthesized in this study via a simple process and then utilized as a novel electrode material to electrochemically detect BZC. With the optimized experimental conditions, the HP-β-CD–CB nanohybrid-modified electrode shows wide linearity from 0.05 to 7.0 μM and very low detection limit (0.015 μM) for BZC detection. In addition, the repeatability, stability, and selectivity as well as practical-sample analysis of the HP-β-CD–CB electrode were investigated, and the observed results are desirable. The superior sensing performances coupled with its advantages including low-cost, simple and highly sensitive detection suggest that HP-β-CD–CB has important potential application for BZC analysis in practical samples.